Complications Following Percutaneous Mitral Valve Repair - Gheorghe, Livia; Ielasi, Alfonso; Rensing, Benno J. W. M.; Eefting, Frank D.; Timmers, Leo; Latib, Azeem; Swaans, Martin J. (Frontiers in Cardiovascular Medicine, 2019)
Mitral valve disease affects more than 4 million people in the United States and it is the second most prevalent valvulopathy in Europe. The gold standard of treatment in these patients is surgical repair or mitral valve replacement. In the last decade numerous transcatheter therapies have been developed to overcome the increased number of subjects with symptomatic severe mitral regurgitation and high surgical risk. The Mitraclip (Abbott Vascular, Menlo Park, CA), the CarillonTM Mitral Contour SystemTM (Cardiac Dimension Inc., Kirkland, WA, USA), the MitralignTM (Mitralign, Tewksbury, Massachusetts) and the Cardioband (Edwards Lifesciences, Irvine, CA) are the principal percutaneous devices for mitral valve repair. We present an evidence-based clinical update that provides an overview of these technologies and their potential complications.